A continuation method for nonlinear complementarity problems over symmetric cones - Chua, Chek Beng. (2011)
In this paper, we introduce a new P-type property for nonlinear functions defined over Euclidean Jordan algebras, and study a continuation method for nonlinear complementarity problems over symmetric cones. This new P-type property represents a new class of nonmonotone nonlinear complementarity problems that can be solved numerically.